PENGARUH PEMBERIAN DOSIS PUPUK UREA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI PUTIH (BRASSICA CHINENSIS L.) DALAM MEDIA POLYBAG - Yoveeta Yasinta Boli; Oktaviana Rosario Sere Gili (Fakultas Pertanian, Universitas Nusa Nipa, 2023)
This study aims to examine the influence of urea fertilizer doses on the growth and yield of white mustard (Brassica chinensis L.) cultivated in polybags. The research was conducted in Nangameting Village, Alok Timur District, from March to April 2023. The experimental design used was a Randomized Complete Block Design (RCBD) with five treatments and four replications, totaling 20 experimental units. The treatments included control (no fertilizer), and urea doses of 1 g, 3 g, 5 g, and 7 g per polybag. The variables observed were plant height, number of leaves, and fresh weight of the plants. Data analysis was performed using ANOVA, followed by Least Significant Difference (LSD) test at 5% significance level. The results indicated that urea fertilizer significantly affected plant height and the number of leaves at 28 days after planting. The dose of 1 g/polybag produced the highest plant height, while the 3 g/polybag dose resulted in the highest fresh weight. The findings suggest that appropriate urea fertilization can enhance the vegetative growth and yield of white mustard in polybags, with further research needed to determine optimal fertilizer doses and application timing.